Peritoneal Tuberculosis in Pregnancy: A Rare Occurrence - Anand, Priti; Bindra, Mukul (International Journal of Applied Sciences and Biotechnology, 2014)
Extrapulmonary tuberculosis is least common form of tuberculosis in pregnancy, early diagnosis of which will help to reduce maternal and neonatal morbidity and mortality. My patient is 25 years old primigravida admitted with Ascitis, Anorexia, low grade fever on and off. Diagnosed as peritoneal tuberculosis after abdominal fluid sent for AFB culture. Patient was given Antitubercular treatment. Ascitic fluid gradually declined and pregnancy moved on but patient landed up in preterm labour and delivered baby which the pediatrician was unable to save because of extreme prematurity. DOI: http://dx.doi.org/10.3126/ijasbt.v2i3.11117 Int J Appl Sci Biotechnol, Vol. 2(3): 371-372